Bibliometric analysis of innovation in Mexico (2021)
Abstract This article aims to use bibliometric techniques to analyze the production of scientific documents related to innovation research carried out in the territory of Mexico. The study focuses on a period of thirty-eight years, from 1980 to 2019. Knowing the direction that innovation takes in Mexico during this period is what motivates its implementation. The main source of information for this study is the "Web of Science" database. The results show an exponential increase in publications starting in 2010, with the participation of Spanish- or English-speaking authors; more research on innovation in the areas of health; the adoption of a broader concept of innovation; and language as a limiting factor for collaborations. Key Words: Bibliometrics, Innovation, Mexico, Web of Science. JEL codes: O32, Y10, Z00 Received: 21/07/2020.  Accepted: 12/04/2021.  Published: 01/06/2021.